Quelle place pour l'esprit critique à l'École ? Étude d'un dispositif éducatif dit d'«éducation par la recherche » - Filippo Pirone (Nantes Université, 2024)
Influenced by OECD's recommendations according to which critical thinking would be one of the most important 21st century learning skills, French education system lately promoted educational dispositives more or less explicitly related to this transversal skill. Through a sociologic point of view and by discussing some outcomes of a qualitative survey within one of these dispositives, this paper aims at questioning the scope of critical thinking within contemporary French education system. The outcomes show that the pedagogisation of critical thinking as a school object at the service of pupils' intellectual development is still in its infancy. In fact, this skill is neither a focus nor an object taught by School, but rather a prerequisite requirement. This can gender difficulties and misunderstandings, particularly for pupils who are the less familiar with the School culture's normativity.